Inhibition of indoleamine 2, 3‐dioxygenase activity enhances the anti‐tumour effects of a Toll‐like receptor 7 agonist in an established cancer model. Issue 4 (April 2015) - Ito, Hiroyasu; Ando, Tatsuya; Arioka, Yuko; Saito, Kuniaki; Seishima, Mitsuru
Summary Toll‐like receptor (TLR) agonists have been shown to have anti‐tumour activity in basic research and clinical studies. However, TLR agonist monotherapy does not sufficiently eliminate tumours. Activation of the innate immune response by TLR agonists is effective at driving adaptive immunity via interleukin‐12 (IL‐12) or IL‐1, but is counteracted by the simultaneous induction of immunosuppressive cytokines and other molecules, including IL‐10, transforming growth factor‐β, and indoleamine 2, 3‐dioxygenase (IDO). In the present study, we evaluated the anti‐cancer effect of the TLR7 agonist, imiquimod (IMQ), in the absence of IDO activity. The administration of IMQ in IDO knockout (KO) mice inoculated with tumour cells significantly suppressed tumour progression compared with that in wild‐type (WT) mice, and improved the survival rate. Moreover, injection with IMQ enhanced the tumour antigen‐specific T helper type 1 response in IDO‐KO mice with tumours. Combination therapy with IMQ and an IDO inhibitor also significantly inhibited tumour growth. Our results indicated that the enhancement of IDO expression with TLR agonists in cancer treatment might impair host anti‐tumour immunity while the inhibition of IDO could enhance the therapeutic efficacy of TLR agonists via the increase of T helper type 1 immune response.